The Global Revival of Legendism: Korean Online Games - Bainbridge, William Sims (International journal for the study of new religions, 2021)
In the context of modern secularization, Legendism can be defined as a cultural form adjacent to traditional religion, taking supernatural narratives seriously but not devoting faith or authority to them. Design teams in South Korea have been creating massively multiplayer online games inspired significantly by the folk religion of their country, but well-integrated into the cultural diversity of their worldwide audience. Extensive description of the first case provides a conceptual grounding for the others, based on both qualitative ethnography and quantitative collection of statistics. With that introduction, the diversity of games is demonstrated through brief consideration of five others. Deeper explorations of two currently very popular theocratic virtual worlds affirm the continuing significance of Korean integration into legendary global culture. Primary themes include the relationship between magic and religion, the personal characteristics attributed to avatars and deities, and the cultural dynamics of globalization.